Oxygen reserve index guided oxygen titration in one lung ventilation with low fresh gas flow - SARAÇOĞLU, AYTEN; YILDIZELİ, BEDRETTİN; YÜKSEL, MUSTAFA; AYKAÇ, ZEYNEP ZUHAL (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Continuous oxygen reserve index (ORI) measurement with multiple wave pulse co-oximetry is a noninvasive measurement. The decrease in the ORI trend provides a prediction for the development of hypoxemia and provides information on hyperoxia. Our aim is to determine the effect of ORI-guided oxygen titration on hyperoxemia-mediated morbidity. Materials and methods: Consecutive 120 ASA I-III patients, 18-70 years of age, without severe obstruction or restriction, undergoing one lung ventilation (OLV), were included in the study. Patients were divided into 4 groups. Oxygen titration without ORI monitoring with low-flow anesthesia (1 L/min, Group 1, n = 25) and high-flow anesthesia (4 L/min, Group 2, n = 28). Oxygen titration by ORI monitoring with low flow anesthesia (1 L/min, Group 3, n = 25) and high flow anesthesia (4 L/min, Group 4, n = 25). FiO(2) increased up to 100% if necessary. OLV time, duration of surgery and anesthesia, FiO(2) applied during OLV, oxygen application time (T) over 60%, vital signs, hospital and ICU stay time, and complications were recorded. Results: There was a statistically significant difference in terms of FiO(2) used during OLV (p < 0.05). There was no difference in ORI values (p < 0.05). In Group 3, both PaO2 and SpO(2) were significantly lower than the others both before and during OLV. There was no significant difference in terms of ORI parameters between low flow and high flow anesthesia groups. There was a strong, positive correlation between the duration of hospital stay and FiO(2) used above 80% during OLV. Conclusion: We concluded that ORI-guided thoracic anesthesia may reduce hospital stay and increase patient safety.
Keywords: Oxygen reserve index; thoracic surgery; one lung ventilation; low flow anesthesia; COMPLICATIONS